Closed-loop Modulation of the Self-regulating Brain: A Review on Approaches, Emerging Paradigms, and Experimental Designs. (10th February 2022) - Farkhondeh Tale Navi, Farhad; Heysieattalab, Soomaayeh; Ramanathan, Dhakshin S.; Raoufy, Mohammad Reza; Nazari, Mohammad Ali
Highlights: Closed-loop systems have been used for investigating the brain–behavior relationship. Closed-loop neuromodulation is a novel approach in the brain stimulation paradigms. Closed-loop experimental designs are drawing attention in the field of neurofeedback. Abstract: Closed-loop approaches, setups, and experimental designs have been applied within the field of neuroscience to enhance the understanding of basic neurophysiology principles (closed-loop neuroscience; CLNS) and to develop improved procedures for modulating brain circuits and networks for clinical purposes (closed-loop neuromodulation; CLNM). The contents of this review are thus arranged into the following sections. First, we describe basic research findings that have been made using CLNS. Next, we provide an overview of the application, rationale, and therapeutic aspects of CLNM for clinical purposes. Finally, we summarize methodological concerns and critics in clinical practice of neurofeedback and novel applications of closed-loop perspective and techniques to improve and optimize its experiments. Moreover, we outline the theoretical explanations and experimental ideas to test animal models of neurofeedback and discuss technical issues and challenges associated with implementing closed-loop systems. We hope this review is helpful for both basic neuroscientists and clinical/ translationally-oriented scientists interested in applying closed-loop methods to improve mental health and well-being.